Implikasi Yuridis Ambang Batas Terhadap Pengajuan Permohonan Sengketa Pilkada - Ade Mazhar Amin Bahri (Lex Renaissance, 2020)
One of the mandatory requirements to submit an acceptable lawsuit of dispute over the election results (PHP) is the threshold set out in Article 158 paragraph (1) and (2) of Law No. 10 of 2016, which after the enactment of this regulation, most of the PHP submitted before the Constitutional Court (MK) are deemed unacceptable as they do not meet the said threshold. This research analyses two problem formulations: first, what is the concept used in setting the threshold for submission of regional election dispute? Second, what are the juridical implications of Article 158 paragraph (1) and (2) of Law Number 10 of 2016 on Regional Elections for filing lawsuit of election disputes? This study uses a normative method with a statutory approach. The results of the study conclude that first, the application for a dispute over the election results must be based on the number of residents in the province conducting the election with the threshold concept or difference in votes based on a predetermined percentage. Second, there is a good number of regions that the Constitutional Court cannot accept because they do not fulfill the threshold concept. This study recommends the need for refinement and renewal of legal rules for the 2027 simultaneous regional elections while at the same time considering a sense of justice for the candidate-pairs of Head of District.